Natural cytotoxicity impairment in familial haemophagocytic lymphohistiocytosis. Issue 3 (March 1988) - Aricò, M; Nespoli, L; Maccario, R; Montagna, D; Bonetti, F; Caselli, D; Burgio, G R
Abstract : Ten children with the characteristic clinical and haematological features of haemophagocytic lymphohistiocytosis are reported. Four patients treated with a combination of drugs comprising etoposide, methotrexate, and steroids were in complete remission after 10 to 30 months. Natural cytotoxic mechanisms including natural killer cell activity, antibody dependent cell mediated cytotoxicity, lymphokine activated killer cell activity, and natural killer cell like activity were persistently absent or severely impaired in these four patients despite their clinical remission. Their parents and one healthy sibling also had impaired natural cytotoxic mechanisms. Constitutional impairment of natural cytotoxic mechanisms could be important in the pathogenesis of haemophagocytic lymphohistiocytosis.